Expanding the Conceptualisations of Citizenship Norms—A Qualitative Study of Young Poles and Their Parents - Weronika Najda; Stuart Hanmer-Lloyd (Societies)
Research shows that the way people define a good citizen can influence their political participation. However, the well-known binary concept of ‘engaged’ and ‘duty-based’ citizenship, used in mass surveys, does not apply to the majority of studied populations; therefore, its usefulness can be disputed. Such social norms of citizenship can also change over time and this process can be profound in countries that undergo a political system change, like Poland in the 1980–90s. To gain insight into how Poles understand citizenship, and how the engaged/duty-based concept applies to them, we interviewed 32 Poles—young people and their parents. Our analysis shows that the standard conceptualisation would have not accounted for two key elements of our participants’ understanding of citizenship—a ‘character’ and a ‘patriotic’ component. This finding demonstrates the continuing impact of moral values and the salience of the national context. In particular, parents and inactive young people based their definitions on these two components. Active young people, on the other hand, chose all-encompassing citizenship norms, mixing engaged, duty-based, patriotic and character elements in their normative repertoire.